ChemInform Abstract: A Highly Chemoselective and Practical Alkynylation of Thiols. Issue 49 (3rd December 2013) - Frei, Reto; Waser, Jerome
Abstract A thiol‐alkynylation procedure applies a hypervalent iodine alkyne agent and can be applied to a wide range of aromatic, aliphatic, heteroaromatic thiols as well as to cysteines and peptides.